2016
DOI: 10.1890/15-2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endosymbionts protect aphids in the field and alter parasitoid community composition

Abstract: It has become increasingly evident that many organisms rely on microbial symbionts for defense against natural enemies, but the ecological importance of defensive symbionts for natural communities still needs to be investigated. A well-known example is Hamiltonella defensa, a heritable endosymbiotic bacterium commonly found in aphids. Laboratory experiments have shown that H. defensa strongly protects aphids against parasitic wasps (parasitoids), although this protection is not equally effective against differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 57 publications
4
88
2
Order By: Relevance
“…In addition, inbreeding in parasitoids can significantly influence their biology, including host selection behaviour (Sepúlveda et al, 2016) and it is possible that outbred individuals may respond differently to endosymbiont defence or to hyperparasitoid attack. However, field experiments suggest that aphids are protected by symbionts against natural parasitoid populations in a similar manner to that observed in the laboratory Rothacher et al, 2016), and it is likely that the results reported in this study will also pertain in natural conditions.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In addition, inbreeding in parasitoids can significantly influence their biology, including host selection behaviour (Sepúlveda et al, 2016) and it is possible that outbred individuals may respond differently to endosymbiont defence or to hyperparasitoid attack. However, field experiments suggest that aphids are protected by symbionts against natural parasitoid populations in a similar manner to that observed in the laboratory Rothacher et al, 2016), and it is likely that the results reported in this study will also pertain in natural conditions.…”
Section: Discussionsupporting
confidence: 73%
“…No laboratory or field cage experiments previously undertaken in the aphid symbiont system have yet included hyperparasitoids, although they can be an extremely important source of parasitoid mortality in the field (Müller et al, 1999). A previous field experiment has shown no differences between aphids with and without symbionts in their rates of secondary parasitism Rothacher et al, 2016), although hyperparasitoid sample sizes were small. The fact that the relative benefits of a symbiont can vary depending on the wider community present shows that we need to consider the food web context when seeking to explain the patterns of symbiont distribution we observe in nature (Ferrari et al, 2012;Russell et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symbionts, aphids, plants, natural enemies and the environment are all directly or indirectly associated with each other composing a reticular structure (Figure 2) and the defensive symbionts may have the potential to alter the food web structure and dynamics (Rothacher et al, 2016;Hrček et al, 2016).…”
Section: Symbionts Interactions With Biotic and Abiotic Environmentmentioning
confidence: 99%